Imagens da prostituicão na belle epoque paulistana - Rago, Luzia Margareth (2005)
AbstractNew content and cultural significance were attached to the practices of prostitution in Brazil, during the transition of the tradicional slave society to one of free-labor. The construction of prostitution as a “social evil” by medical and criminological discourses aimed at defining moral codes of social and sexual behavior that guided girls’ inscription in the public sphere. In a moment of massive industrialization, we register a growing participation of girls working in factories and other urban activities. On the other hand, like the immigrant worker, the prostitute was invested with images of positivity: both represented the civilizing ideal of the country’s entry into modernity. If prostitution could mean the threat of rich and poor girls’ corruption, it also signified the new conquests and the introduction of new habits and customs from modern societies to a Brazil recently emerged from slavery. The construction of girls’ identity mobilized new representations of female body - from the ideal of pureness to the prostitute’s perverse sexuality. In the same way, it was associated with the political metaphor of the youth of the nation where everyting was to be constructed